Fibroblast growth factor 19 regulates polycystic ovary syndrome progression via FGFR4-ERK-NRF2 pathway - Qu, Junjie; Qiu, Meiting; Wang, Jingyun; Chen, Zhiqin; Chen, Miaoxin; Teng, Xiaoming; Li, Yiran (Frontiers in Cell and Developmental Biology, 2025)
BackgroundFGF19, an endocrine hormone, participating in ovarian function. This study investigated the roles of FGF19 in polycystic ovary syndrome (PCOS) and its associated molecular mechanisms, specifically focusing on the FGFR4-ERK-NRF2 pathway.MethodsClinical samples were collected to determine FGF19 levels, and proteomic analysis was performed on follicular fluid. A mouse model was established to investigate the molecular pathogenesis of PCOS. Subsequently, a series of in vitro experiments explored the effects and mechanisms of FGF19 on PCOS with and without oxidative stress.ResultsProteomics identified 144 differentially expressed proteins enriched in pathways including VEGF, PPAR, IL-2-STAT5, mTORC1, epithelial-mesenchymal transition, bile acid metabolism, and oxidative phosphorylation. FGF19/FGF15 levels were significantly higher in PCOS patients and mice compared to controls. In PCOS mice, FGFR4, NRF2, and HO1 were upregulated, while p-ERK/ERK levels were decreased. FGF19 overexpression promoted KGN cells viability while inhibiting apoptosis, upregulating FGFR4, NRF2, HO1, BCL2, and p-ERK/ERK, and downregulating BAX. However, LY3214996 reversed the action of FGF19 overexpression in KGN cells. H2O2 treatment decreased KGN cell viability, increased apoptosis, and elevated ROS levels. NRF2 knockdown further aggravated H2O2’s effectd, whereas FGF19 overexpression countered the changes in viability, apoptosis, and ROS levels caused by H2O2. Furthermore, H2O2 stimulation upregulated BAX, NRF2, and HO1, while decreasing BCL2 and p-ERK/ERK levels; NRF2 knockdown further upregulated BAX and downregulated BCL2 and p-ERK/ERK. Conversely, FGF19 overexpression had opposite effects on NRF2 knockdown.ConclusionFGF19 may be involved in PCOS occurrence and development through the regulation of the FGFR4-ERK-NRF2 pathway.